Selective laser melting of a high strength AlMnSc alloy: Alloy design and strengthening mechanisms. (1st June 2019) - Jia, Qingbo; Rometsch, Paul; Kürnsteiner, Philipp; Chao, Qi; Huang, Aijun; Weyland, Matthew; Bourgeois, Laure; Wu, Xinhua
Abstract: Additive manufacturing, or 3D printing, has brought tremendous opportunities for the design and making of metallic components with high geometrical complexity. However, in order to maximize the performance and functionality of a specific part, the additive manufacturing industry currently still faces fundamental issues of material processability and limited mechanical properties. Here, we report a high strength in-process and post-process friendly Al alloy specifically developed for the selective laser melting (SLM) process, one of the most commonly used additive manufacturing techniques. We found that the introduction of Mn and Sc as major strengthening elements significantly improved the processability of the Al alloy and its corresponding mechanical properties due to the rapid solidification nature of the SLM process. The developed alloy demonstrates an exceptional high thermal stability, which enables the utilization of a very simple post heat treatment to relieve the residual stresses generated during the SLM process, maintain a high solid solution strengthening effect from Mn and simultaneously achieve exceptional precipitation strengthening from a high density of nano-sized Al3 Sc precipitates. We created a new high strength Al alloy with a yield strength of up to 560 MPa and a ductility of about 18% after a simple industrially desirable post heat treatment of 5 h at 300 °C. The highly enhanced alloy properties, good processability and simple post heat treatment of the developed alloy offers tremendous benefits for the fabrication of complex high performance lightweight engineering components made by SLM. Graphical abstract: Image 1